2018
DOI: 10.1105/tpc.18.00321
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Protein RBP-P Is Required for Glutelin and Prolamine mRNA Localization in Rice Endosperm Cells

Abstract: In developing rice () endosperm, mRNAs of the major storage proteins, glutelin and prolamine, are transported and anchored to distinct subdomains of the cortical endoplasmic reticulum. RNA binding protein RBP-P binds to both glutelin and prolamine mRNAs, suggesting a role in some aspect of their RNA metabolism. Here, we show that rice lines expressing mutant RBP-P mislocalize both glutelin and prolamine mRNAs. Different mutant RBP-P proteins exhibited varying degrees of reduced RNA binding and/or protein-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 72 publications
(128 reference statements)
1
70
1
Order By: Relevance
“…The interrelatedness of the three RNA transport pathways suggests that they share common trans-factors for targeting to the ER membrane, while glutelin and prolamine pathways require additional factors for selective transport (Chou et al, 2019). Indeed, our studies showed that prolamine and glutelin zipcode sequences bind identical transfactors, Tudor-SN (Chou et al, 2017;Tian et al, 2018, 2019), RBP-P (Chou et al, 2017; Tian et al, 2018, 2019), and RBP-L (Chou et al, 2017;Tian et al, 2018Tian et al, , 2019.…”
Section: Mrna Localization In Plant Cellsmentioning
confidence: 65%
See 3 more Smart Citations
“…The interrelatedness of the three RNA transport pathways suggests that they share common trans-factors for targeting to the ER membrane, while glutelin and prolamine pathways require additional factors for selective transport (Chou et al, 2019). Indeed, our studies showed that prolamine and glutelin zipcode sequences bind identical transfactors, Tudor-SN (Chou et al, 2017;Tian et al, 2018, 2019), RBP-P (Chou et al, 2017; Tian et al, 2018, 2019), and RBP-L (Chou et al, 2017;Tian et al, 2018Tian et al, , 2019.…”
Section: Mrna Localization In Plant Cellsmentioning
confidence: 65%
“…RBP-P contains two RRMs flanked by Ala/Glu-rich N-terminal and Gly-rich C-terminal domains. The two RRMs in RBP-P directly contribute to its strong binding to glutelin and prolamine mRNAs (Tian et al, 2018). The auxiliary domains flanking the RRMs, especially the Gly-rich region, mediated both RNA binding and protein-protein interaction (Tian et al, 2018).…”
Section: Identification Of Trans-factors That Recognize Storage Protementioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy (TEM) analysis was performed as previously described (Tian and Sun 2011;Tian et al, 2018).…”
Section: Microscopy Analysismentioning
confidence: 99%